Niveles de compost de estiércol de aves de postura y sus efectos en el cultivo de Brassica napus L. nabo, en Zungarococha-Loreto.2022 - Pizango Amuño, Fidel (2023)
The study of manure compost levels of laying birds in Brassica napus L. turnip, took place in Zungarococha. The statistical design was the DBCA finding results that defined the study: The Treatment with 30 t of compost of manure of laying birds (T4), obtained outstanding results in the characteristics and yield of the crop with statistical significances. The results were 40 and 58 cm in height and width of plant; the number and weight of leaves/plant were 16 units and 303 g; the weight of plant of 750 g, the length and diameter of root of 26 and 7 cm. The yield of root and roots/ha, were 445 g and 44,500 Kg. The best utility was obtained by the T4 with S/.39,742.8.